IMPLEMENTATION SERVICE RIGHT ASSIMILATION IN HOUSE FOR PRISONERS DURING THE COVID PANDEMIC 19IN CLASS IIA PURWOKERTO PRISON - Ervan Miftahul Alim; Taufik Purboyo; Emiraldo Win.P (Department of Public Administration, University Wijaykusuma Purwokerto, 2022)
This study is entitled